What Is the Role of Parents, Teachers, and Peers in Shaping Adolescent Sexual Behavior? - Nurkhansa, Thifal; Husna, Qisty Dzakiyyatu; Umaroh, Ayu Khoirotul (Nur Science Institute and Perkumpulan Keluarga Berencana Indonesia (PKBI) Semarang, 2024)
Background: Premarital sexual activity among adolescents is a growing public health concern in Indonesia. Adolescents often rely on parents, teachers, and peers as primary sources of reproductive health information. However, their influence on sexual behavior remains underexplored in large-scale national surveys. This study aims to analyze the relationship between reproductive health information sources and adolescent sexual behavior using data from the 2017 Indonesian Demographic and Health Survey (SDKI). Methods: A cross-sectional design was used with a quantitative approach, involving 10,643 unmarried adolescents aged 15–24 years. Data were analyzed using descriptive statistics and Chi-square tests to assess associations between information sources (parents, teachers, and peers) and adolescent sexual behavior Results: The results of this study showed that (There was a significant relationship between information sources from parents (p = 0.000), teachers (p = 0.003), and peers (p = 0.000) and adolescent sexual behavior.Implications: Strengthening communication between parents and children, optimizing the role of teachers in reproductive health education, and empowering peer groups can contribute to reducing risky sexual behaviors in adolescents.